The border resident in Brazilian migration legislation (Revista do Tribunal Regional Federal da 3ª Região, 2025)
The article addresses the legal evolution of the border resident institute in Brazilian migration legislation, analyzing normative transformations from Decree-Law No. 7,967/1945 to the Migration Law (Law No. 13,445/2017). It aims to investigate how different political paradigms — from national security to human rights — were reflected in the legal treatment of border residents and how current regulation has been implemented by the Executive Branch. It employs bibliographic and documentary research methodology, with qualitative analysis of national legislation, international agreements, regulatory decrees, and specialized doctrinal production. It concludes that the Migration Law promoted significant paradigmatic change by recognizing the complex reality of border regions, expanding rights and facilitating regional integration, although challenges persist in the practical implementation of border residents' rights, especially regarding federative articulation to guarantee essential public services and the need for specific policies that consider the peculiarities of cross-border dynamics.
Keywords: migration; border resident; migration law; human rights; regional integration